Acute phase markers in CSF reveal inflammatory changes in Alzheimer's disease that intersect with pathology, APOE ε4, sex and age. (March 2021) - Ayton, Scott; Janelidze, Shorena; Roberts, Blaine; Palmqvist, Sebastian; Kalinowski, Pawel; Diouf, Ibrahima; Belaidi, Abdel A.; Stomrud, Erik; Bush, Ashley I.; Hansson, Oskar
Highlights: Inflammatory acute phase proteins in CSF were measured in an Alzheimer's cohort. Acute phase proteins elevated with clinical progression of Alzheimer's disease. Acute phase proteins were not elevated by the presence of plaque (Aβ42 /t-tau). P-tau181 mediated elevated acute phase proteins. APOE ε4, sex and age had complex interactions with acute phase proteins. Abstract: It is unknown how neuroinflammation may feature in the etiology of Alzheimer's disease (AD). We profiled acute phase response (APR) proteins (α1-antitrypsin, α1-antichymotrypsin, ceruloplasmin, complement C3, ferritin, α-fibrinogen, β-fibrinogen, γ-fibrinogen, haptoglobin, hemopexin) in CSF of 1291 subjects along the clinical and biomarker spectrum of AD to investigate the association between inflammatory changes, disease outcomes, and demographic variables. Subjects were stratified by Aβ42 /t-tau as well as the following clinical diagnoses: cognitively normal (CN); subjective cognitive decline (SCD); mild cognitive impairment (MCI); and AD dementia. In separate multiple regressions (adjusting for diagnosis, age, sex, APOE -ε4) of each APR protein and a composite of all APR proteins, CSF Aβ42 /t-tau status was associated with elevated ferritin, but not any other APR protein in CN and SCD subjects. Rather, the APR was elevated along with symptomatic progression (CN < SCD < MCI < AD), and this was elevation was mediated by CSF p-tau181. APOE ε4 status did not affect levels of any APR proteins in CSF, while these were elevated in males and with increased age. The performance of the APR in predicting clinical diagnosis was influenced by APOE ε4 status, sex, and age. These data provide new insight into inflammatory changes in AD and how this intersects with pathology changes and patient demographics.